1983
DOI: 10.2527/jas1983.561139x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Profiles of LH, FSH and Prolactin from 10 Weeks of Age until Puberty in Gilts2

Abstract: To characterize the secretory patterns of luteinizing hormone (LH), follicle stimulating hormone (FSH) and prolactin (PRL) during prepubertal development of the gilt, blood samples were collected at 20-min intervals for 4 h once a week from four littermate gilts 10 to 18 wk of age and from another group of four littermate gilts 19 to 25 wk of age. Puberty occurred in the latter group during wk 25. Serum concentrations of LH, FSH and PRL were averaged for each 4-h sampling period within each gilt, and any singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
3
4

Year Published

1984
1984
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 0 publications
2
20
3
4
Order By: Relevance
“…In women, baboons and monkeys, plasma relaxin also increases after human chorionic gonadotropin (hCG) administration (Quagliarello et al 1980, Castracane et al 1983, Ottobre et al 1984. Although cyclic or exogenous gonadotropins were absent in the present study, we cannot rule out the possibility that follicular relaxin production is influenced by the low circulating levels of gonadotropins reported in prepubertal gilts (Colenbrander et al 1982, Diekman et al 1983, Grieger et al 1986.…”
Section: Discussioncontrasting
confidence: 46%
“…In women, baboons and monkeys, plasma relaxin also increases after human chorionic gonadotropin (hCG) administration (Quagliarello et al 1980, Castracane et al 1983, Ottobre et al 1984. Although cyclic or exogenous gonadotropins were absent in the present study, we cannot rule out the possibility that follicular relaxin production is influenced by the low circulating levels of gonadotropins reported in prepubertal gilts (Colenbrander et al 1982, Diekman et al 1983, Grieger et al 1986.…”
Section: Discussioncontrasting
confidence: 46%
“…Diekman et al (1983) from 10 to 25 wk of age and by Camous et al (1985) from2 to 28 wk of age. It has previously been suggested that the transitory increase in LH Plasma profiles of estradiol as observed in this study differ markedly from the pattern of urinary estrone excretion as reported by Camous et al (1985).…”
mentioning
confidence: 99%
“…However, these authors reported increased prepubertal FSH secretion, which began to decline only at 125 days of age (equivalent to the second weight group of the present study). A decline in FSH secretion from as early as 70 days of age has been reported in gilts (Diekman et al, 1983) …”
Section: Oestradiolmentioning
confidence: 92%